2022
DOI: 10.1101/2022.10.07.511119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The fate of recessive deleterious or overdominant mutations near mating-type loci under partial selfing

Abstract: Large regions of suppressed recombination having extended with time occur in many organisms around genes involved in mating compatibility (sex-determining or mating-type genes). The sheltering of deleterious alleles has been proposed to be involved in such expansions. However, the dynamics of deleterious mutations partially linked to genes involved in mating compatibility are not well understood, especially in finite populations. In particular, under what conditions deleterious mutations are likely to be main… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 94 publications
2
5
2
Order By: Relevance
“…The more often that deleterious mutations segregate in genomes then the more this effect can act: a given fragment evolving recombination cessation and capturing a permanently heterozygous allele will have a greater chance of having a higher fitness differential with the average locus if the distribution of the number of deleterious mutations in this fragment is wider in the population, resulting in stronger selection (Jay et al ., 2022). We found that TEs did not accumulate preferentially in the margin of the non-recombining regions, in contrast to our prediction based on a recent theoretical model showing that, in automictic species such as Microbotryum fungi, a mating-type locus can shelter deleterious mutations in its flanking regions (Tezenas et al ., 2022). As TE insertions can be deleterious, one may have expected that selfing would have promoted their purge more easily farther away from the mating-type locus (Tezenas et al ., 2022).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The more often that deleterious mutations segregate in genomes then the more this effect can act: a given fragment evolving recombination cessation and capturing a permanently heterozygous allele will have a greater chance of having a higher fitness differential with the average locus if the distribution of the number of deleterious mutations in this fragment is wider in the population, resulting in stronger selection (Jay et al ., 2022). We found that TEs did not accumulate preferentially in the margin of the non-recombining regions, in contrast to our prediction based on a recent theoretical model showing that, in automictic species such as Microbotryum fungi, a mating-type locus can shelter deleterious mutations in its flanking regions (Tezenas et al ., 2022). As TE insertions can be deleterious, one may have expected that selfing would have promoted their purge more easily farther away from the mating-type locus (Tezenas et al ., 2022).…”
Section: Discussioncontrasting
confidence: 99%
“…We found that TEs did not accumulate preferentially in the margin of the non-recombining regions, in contrast to our prediction based on a recent theoretical model showing that, in automictic species such as Microbotryum fungi, a mating-type locus can shelter deleterious mutations in its flanking regions (Tezenas et al ., 2022). As TE insertions can be deleterious, one may have expected that selfing would have promoted their purge more easily farther away from the mating-type locus (Tezenas et al ., 2022). Not all TE insertions are however deleterious and their active spread may counteract the purging effect.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Deterministic models by Strobeck (1980) and Leach et al (1986) showed that even lethal mutations can be effectively sheltered, provided they are tightly linked to strongly balanced allelic lines. More recently, Tezenas et al (2022) observed that linkage to a mating-type locus, such as found in some fungi (where typically two strongly balanced allelic lines segregate), decreases the probability and increases the time for purging of linked deleterious mutations. Stochastic simulations by Llaurens et al (2009) further predicted that the sheltering of deleterious recessive mutations should be related to the number of balanced allelic lines, with higher probabilities of fixation of deleterious alleles within an allelic line when the number of alleles increases.…”
Section: Introductionmentioning
confidence: 99%